Penggunaan Games Dan Ice Breaking Dalam Pembelajaran - Miftahul Hamdi; Amir Syarifudin; Muhammad (Lembaga Pendidikan Al-Gafari, 2023)
The use of games and icebreakers in the learning process has been widely researched and has been proven to be able to increase students' curiosity and learning motivation because this method is fun so that students are not too focused and tense in learning. In this paper, the author uses a qualitative method, namely the literature review model where the author uses several previous studies as references in the form of papers, articles, or journals. However, apart from providing positive benefits, this technique also has several weaknesses, such as taking a lot of time and requiring high creativity.